A review of surgical and peri‐operative factors to consider in emergency laparotomy care. (5th January 2020) - Boyd‐Carson, H.; Gana, T.; Lockwood, S.; Murray, D.; Tierney, G. M.
Summary: Patients undergoing emergency laparotomy are a heterogeneous group with regard to comorbidity, pre‐operative physiological state and surgical pathology. There are many factors to consider in the peri‐operative period for these patients. Surgical duration should be as short as possible for adequate completion of the procedure. This is of particular importance in the elderly and comorbid population. To date, there are limited data addressing the role of damage control surgery in emergency general surgery. Dual consultant‐led care in all stages of emergency laparotomy care is increasing, with increased presence out of hours and also for high‐risk patients. The role of the stoma care team should be actively encouraged in all patients who may require a stoma. Due to the emergent and unpredictable nature of surgical emergencies, healthcare teams may need to employ novel strategies to ensure early input from the stoma care team. It is important for all members of the medical teams to ensure that patients have given consent for both anaesthesia and surgery before emergency laparotomy. Small studies suggest that patients and their families are not aware of the high risk of morbidity and mortality following emergency laparotomy before operative intervention. Elderly patients should have early involvement from geriatric specialists and careful attention paid to assessment of frailty due to its association with mortality and morbidity. Additionally, the use of enhanced recovery programmes in emergency general surgery has been shown to have some impact in reducing length of stay in emergency surgical patients. However, the emergent nature of this surgery has been shown to be a detrimental factor in full implementation of enhanced recovery programmes. The use of a national database to collect data on patients undergoing emergency laparotomy and their processes of care has led to reduced mortality and length of stay in the UK. However, internationally, fewer data are available to draw conclusions.